1996
DOI: 10.1111/j.1752-1688.1996.tb03471.x
|View full text |Cite
|
Sign up to set email alerts
|

SIMULATION OF TEMPORAL CHANGES IN RAINFALL‐RUNOFF CHARACTERISTICS, COON CREEK BASIN, WISCONSIN1

Abstract: Streamflow for 67 years was simulated for Coon Creek at Coon Valley, Wisconsin, for three conditions in the drainage basin: (1) conditions in the 1930s; (2) conditions in the 1970s, excluding flood‐detention reservoirs; and (3) conditions in the 1970s, including flood‐detention reservoirs. These simulations showed that the changes in agricultural practices over 40 years (1940–80) reduced the 100‐year flood by 53 percent (from 38,900 to 18,300 cubic feet per second). The flood‐detention reservoirs reduced the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…HUANG ET AL. Krug, 1996;Bonta et al, 1997;Kang et al, 1998;Wong and Li, 1999;Cheng and Wang, 2002;Rodriguez et al, 2003). Simulation modelling and the design storm approach have been frequently used to estimate the magnitude and frequency of floods in urban areas, and to evaluate the hydrological effects on the characteristics of stormwater runoff with increasing impervious areas.…”
Section: Introductionmentioning
confidence: 99%
“…HUANG ET AL. Krug, 1996;Bonta et al, 1997;Kang et al, 1998;Wong and Li, 1999;Cheng and Wang, 2002;Rodriguez et al, 2003). Simulation modelling and the design storm approach have been frequently used to estimate the magnitude and frequency of floods in urban areas, and to evaluate the hydrological effects on the characteristics of stormwater runoff with increasing impervious areas.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the hydrographical characteristics of a developed watershed vary in conjunction with the degree of urbanization (Kliment and Matoušková 2009). Previous studies have shown that the affected factors include rainwater loss (Gremillion et al 2000, Cheng et al 2008b, watershed function (Krug 1996, Kang et al 1998, Aronica and Cannarozzo 2000, Cheng and Wang 2002, surface runoff (Boyd et al 1994, Junil et al 1999, Rodriguez et al 2003, runoff volume (Arnell 1982), peak discharge (Huang et al 2008a(Huang et al , 2008b, time to peak (Huang et al 2012) and baseflow (Simmons and Reynolds 1982). However, the hydrological effects of urbanization may be particularly severe in watershed divisions that are vulnerable to the breaking of links in the hydrological cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The impervious areas, increasing in the form of parking lots, streets, roofs, etc. (Lazaro 1976), affect the mechanism of infiltration in the hydrological cycle because rainwater infiltrating into the soil layer near the surface is diminished and simultaneously causes changes of rainwater loss (Gremillion et al 2000), hydrological response (Krug 1996;Kang et al 1998;Singh 1998;Aronica and Cannarozzo 2000;Cheng and Wang 2002), surface runoff (Boyd et al 1994;Bonta et al 1997;Junil et al 1999;Rodriguez et al 2003), runoff volume (Arnell 1982), and base flow (Simmons and Reynolds 1982).…”
Section: Introductionmentioning
confidence: 98%